BENEFITS AND CHALLENGES OF IMPLEMENTING INTEGRATED REPORTING FOR ROYAL SCHIPHOL GROUP – A STUDY FOR SCHIPHOL GROUP TO ACHIEVE THEIR 2050 GOAL OF ZERO EMISSION AIRPORT - Putu Deny Wijaya; Miranda Bens (Diponegoro Journal of Accounting, 2022)
The new corporate reporting tool, integrated reporting, combines financial and non-financial data into a single document. Despite numerous studies describing the potential benefits of integrated reporting, it is still not widely used. One reason for the slow adoption is the lack of empirical evidence demonstrating the actual concreteness of these benefits for firms who choose to use integrated reporting. Through a case study, this paper examines the process of implementing integrated reporting, as well as the benefits and obstacles connected with it. The instance of Royal Schiphol Group in particular is examined in order to show the adoption path and the effects of implementing integrated reporting in a setting. The findings reveal that the adoption of integrated reporting was the consequence of a clear willingness of working together on the part of senior management, and that it has had a decisively good influence both internally and externally.